El desarrollo de la dimensión trascendente en una educación de calidad - Bazán Gayoso, Elizabeth (2010)
Any individual is meant to be fully developed. By being true to the self, the individual will grow in every human dimension. Comprehensive quality education requires the development of the transcendent dimension that deeply connects the individual with itself, with the people, with creation, and God. The full development of this perspective is sanctity, for all people.